Over the mountains are mountains : korean peasant households and their adaptations to rapid industrialization - Sorensen, Clark W. (Korean studies of the Henry M. Jackson School of International Studies., 2013)
A description of the economic and ecological organization of rural Korean domestic groups and an analysis of their adaption to the changes brought about by Korea's rapid industrialization.